A Comprehensive Program Evaluation of the Thesis Boot Camp Implementation: Impact on Thesis Writing Ability and Pedagogical Challenges in English Education at IAIN Palopo - Husnaini; Wahibah; Kalsum; Ermawati (LETS: Journal of Linguistics and English Teaching Studies, 2025)
Thesis writing is a major challenge for undergraduate students, often leading to delays in graduation. This study examines the impact of a Thesis Writing Boot Camp on students’ abilities and identifies the challenges faced by 33 students from the English Language Education Study Program at IAIN Palopo. Using a descriptive quantitative approach, data were collected via questionnaires from 23 respondents. Findings revealed that strongly positive outcomes: a high majority of participants reported satisfaction (73.9% satisfied/very satisfied), found materials relevant (82.6% relevant/highly relevant), and rated facilitators highly (91.3% good/excellent). The program also led to significant self-reported improvements in understanding thesis structure (73.9% improved/significantly improved) and increased writing confidence (65.2% confident/very confident). Mentoring sessions were deemed highly beneficial (82.6% beneficial/highly beneficial), and the program received a strong endorsement (60.9% highly likely to recommend). However, challenges persisted, including insufficient time allocation for some sessions (as noted by 8.7% of respondents), only moderate gains in confidence and understanding among a substantial subgroup (34.8%), and an uncomfortable learning environment for a minority (8.7%). The study concludes that structured, intensive Boot Camp is highly effective, and recommendations are provided for program enhancement, including extending session duration and improving the learning environment to optimize outcomes.